2015
DOI: 10.1016/j.solmat.2014.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Voltage limitation analysis in strain-balanced InAs/GaAsN quantum dot solar cells applied to the intermediate band concept

Abstract: IBSCs. In these cells, the dilute nitrogen in the barrier plays an important role for the strain-balance (SB) of the QD layer region that would otherwise create dislocations under the effect of the accumulated strain. The introduction of GaAsN SB layers allows increasing the light absorption in the QD region by multi-stacking more than 100 QD layers. The photo-generated current density (J L ) versus V OC was measured under varied concentrated light intensity and temperature. We found that the V OC of the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…While this has been demonstrated to be effective, the influence of these low bandgap (compared to the spacers) barriers on the V OC has not been discussed. Low bandgap barriers may lead to a fundamental reduction of the limiting V OC (from E G to the bandgap of the barriers, E B ) [31]. This is why we have decided to use AlGaAs barriers, where E B (1.84 eV) is close to E G (1.88 eV), in order to achieve a good bandgap distribution but avoiding the possibility imposing a lower limit to the V OC .…”
Section: Discussionmentioning
confidence: 99%
“…While this has been demonstrated to be effective, the influence of these low bandgap (compared to the spacers) barriers on the V OC has not been discussed. Low bandgap barriers may lead to a fundamental reduction of the limiting V OC (from E G to the bandgap of the barriers, E B ) [31]. This is why we have decided to use AlGaAs barriers, where E B (1.84 eV) is close to E G (1.88 eV), in order to achieve a good bandgap distribution but avoiding the possibility imposing a lower limit to the V OC .…”
Section: Discussionmentioning
confidence: 99%
“…The 8e − ∕QD doping resulted in the highest V oc of 0.932 V, which can be considered a direct effect from the decreased SRH recombination due to the shift of intrinsic region. 29,40 However, the doping-induced band flattening has weakened the carrier collection due to the decreased electric field in the QD region. This negative effect was directly linked to the reduction of J sc for all doped samples.…”
Section: Doping Effect On Inas/gaas Quantum Dot Solar Cell Performancementioning
confidence: 99%
“…For example, in the case of electron-based type-I systems, the valence band offset (VBO) (see Figure 2) is believed to produce an effective bandgap narrowing in terms of maximum attainable V OC . Under this line of thought, the V OC limitation would be similar to that occurring when a lower bandgap material is used as a barrier material between QD layers [30]. It has been suggested that type-II (staggered band lineup, Figure 2) QDs may be advantageous for the implementation of IBSCs, since they would not cause effective bandgap narrowing [29].…”
mentioning
confidence: 97%